A VVTM volume design method for SMA-13 asphalt mixture
Through the volume design method of vertical vibration compaction method, the problems of SMA mixture in the field density and oil-stone ratio design are solved, the road performance and asphalt usage are optimized, and high temperature performance and water stability are improved.
Patent Information
- Application Number
- CN202211328200.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-10-27
AI Technical Summary
The density of existing SMA mixtures is likely to be greater than the standard density when compacted on site, resulting in reduced void ratios, ruts, oil spreading and other problems. The Marshall compaction method causes aggregate crushing, affecting the accuracy of performance prediction, and it is difficult to determine the optimal oil-stone ratio. , especially for the reasonable design of minerals of different densities.
Using a volume design method based on vertical vibration compaction method, the optimal oil-stone ratio and mineral screen pass rate are determined by measuring physical parameters and grading design, the mix ratio of SMA-13 asphalt mixture is optimized, the asphalt usage is reduced, and the amount of asphalt is increased. Road performance.
It improves the road performance of SMA mixture, reduces the amount of asphalt, simplifies operation, is suitable for large-scale promotion, improves high-temperature performance and water stability, and improves low-temperature deformation resistance.
Smart Images

Figure CN116102293B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of traffic civil engineering, and in particular relates to a SMA-13 asphalt mixture VVTM volume design method. Background Art
[0002] Stone Mastic Asphalt (SMA) is currently mainly determined by the Marshall compaction method. However, a large amount of data has shown that the density of SMA mixtures is very likely to be greater than this standard when compacted on site, resulting in a decrease in the void ratio and the occurrence of rutting and oiling under the designed oil-stone ratio. In addition, the Marshall compaction method forms the mixture by hammering, which leads to serious aggregate crushing after increasing the compaction work. This not only causes serious changes in gradation, but also affects the accuracy of the prediction of actual pavement performance, which is bound to affect the mix design of SMA mixtures and make SMA mixtures unable to achieve optimal performance. Studies have found that the correlation between the Marshall compaction specimens and the engineering properties of the on-site core samples is only about 60%. Obviously, the performance of the specimens formed by the Marshall compaction method cannot represent the actual performance of the pavement, resulting in inaccurate mix design.
[0003] At the same time, the dense skeleton structure of SMA determines its good road performance. The dense skeleton structure is a concept of volume. However, the current SMA mixture proportioning method is based on the median of the recommended gradation range, adjusting the key sieve hole pass rate to obtain an SMA mixture that meets the volume parameter requirements. This undoubtedly adds a lot of work for minerals with different densities, and the obtained gradation may not be optimal. At the same time, the optimal asphalt-stone ratio depends on the total surface area of the mineral material, which is related to the volume of the mineral material particles. Therefore, the optimal asphalt-stone ratio of SMA mixtures using mineral materials of different densities is not the same, which makes it difficult to determine the optimal asphalt-stone ratio. When the same asphalt-stone ratio is used, the asphalt content of the SMA mixture with a larger density of mineral material is relatively large, and it is more prone to oil spills and other diseases. Obviously, it is difficult to reasonably design the dense skeleton structure of mineral material particles for mineral materials of different densities by designing SMA mixtures by mass ratio. Summary of the invention
[0004] The purpose of the present invention is to provide a SMA-13 asphalt mixture VVTM volume design method. The method provided by the present invention adopts a volume design method based on the vertical vibration compaction method (VVTM) for mix design, which can reduce the amount of asphalt, improve the road performance of the asphalt mixture, and is easy to operate and suitable for large-scale promotion and application.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a SMA-13 asphalt mixture VVTM volume design method, wherein the SMA-13 asphalt mixture comprises asphalt, coarse aggregate, fine aggregate, mineral powder and fiber; mastic comprises asphalt, fine aggregate, mineral powder and fiber; asphalt mortar comprises asphalt, mineral powder and fiber; and the method comprises the following steps:
[0007] (1) obtaining physical parameters of the asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose, wherein the physical parameters include the density of asphalt, the apparent relative density and the bulk relative density of the coarse aggregate, the apparent relative density of the fine aggregate, the apparent relative density of the mineral powder, and the specific gravity of the fiber;
[0008] (2) The coarse aggregate includes a first-graded coarse aggregate and a second-graded coarse aggregate. According to the relationship between the skeleton gap ratio of the coarse aggregate and the mass percentage of the first-graded coarse aggregate in the coarse aggregate, within the mass percentage range of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the second-graded coarse aggregate in the coarse aggregate and the skeleton gap ratio of the coarse aggregate are obtained based on the principle that the value of the skeleton gap ratio of the coarse aggregate is relatively minimum; the particle size of the first-graded coarse aggregate is 9.5 to 16 mm, and the particle size of the second-graded coarse aggregate is 4.75 to 9.5 mm;
[0009] (3) According to the relationship between the mechanical properties of the SMA-13 asphalt mixture and the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture, and the relationship between the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of asphalt mortar in the volume of mastic, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate and the volume percentage of asphalt mortar in the volume of mastic are obtained based on the principle of optimizing the mechanical properties of the SMA-13 asphalt mixture; the mechanical properties of the SMA-13 asphalt mixture include one or more of Marshall stability, compressive strength, shear strength and splitting strength;
[0010] (4) according to the relationship between the apparent relative density of mineral powder, the specific gravity of fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the volume percentage of asphalt mortar in the volume of mastic, the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is obtained;
[0011] (5) According to the apparent relative density of the mineral powder, the apparent relative density of the coarse aggregate and the apparent relative density of the fine aggregate, the sieve hole pass rate of the key-grade mineral material is obtained, and the sieve hole pass rate of the key-grade mineral material includes the sieve hole pass rate of the 4.75mm grade mineral material and the sieve hole pass rate of the 0.075 grade mineral material; according to the mass percentage of the first graded coarse aggregate and the sieve hole pass rate of the 4.75mm grade mineral material, the sieve hole pass rate of the 9.5mm grade mineral material is obtained; the sieve hole pass rate of the 16mm grade mineral material is 100%; according to the sieve hole pass rate of the key-grade mineral material, the sieve hole pass rate of the 9.5mm grade mineral material and the sieve hole pass rate of the 16mm grade mineral material, Obtain the remaining recommended gradation sieve hole pass rate of each grade of ore material; the recommended gradation sieve hole pass rate of each grade of ore material includes: 16mm grade ore sieve hole pass rate, 9.5mm grade ore sieve hole pass rate, 4.75mm grade ore sieve hole pass rate, 0.075 grade ore sieve hole pass rate and the remaining recommended gradation sieve hole pass rate of each grade of ore material; the remaining recommended gradation sieve hole pass rate of each grade of ore material includes: 2.36mm grade ore sieve hole pass rate, 1.18mm grade ore sieve hole pass rate, 0.6mm grade ore sieve hole pass rate, 0.3mm grade ore sieve hole pass rate and 0.15 grade ore sieve hole pass rate;
[0012] There is no time sequence restriction between steps (2) to (4) and step (5);
[0013] (6) obtaining an initial oil-to-stone ratio according to the density of asphalt, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; obtaining a fiber content according to the specific gravity of fiber, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; preparing a VVTM specimen by a vertical vibration compaction method according to the initial oil-to-stone ratio, the sieve pass rate of each grade of mineral material of the recommended gradation, and the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder, and fiber in the SMA-13 asphalt mixture; the VVTM specimen includes a first specimen, a second specimen, and a third specimen, the oil-to-stone ratio of the first specimen being 0.2 to 0.4 less than the initial oil-to-stone ratio; the oil-to-stone ratio of the second specimen being the initial oil-to-stone ratio; and the oil-to-stone ratio of the third specimen being 0.2 to 0.4 greater than the initial oil-to-stone ratio;
[0014] (7) determining the gross volume density of the VVTM specimen, and obtaining the physical parameters of the VVTM specimen according to the gross volume density, wherein the physical parameters of the VVTM specimen include the coarse aggregate void ratio, the mineral void ratio and the specimen void ratio; when the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, selecting the oil-stone ratio of the VVTM specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen as the optimal oil-stone ratio of the SMA-13 asphalt mixture; the design standard of the vertical vibration compaction method includes: the coarse aggregate void ratio of the VVTM specimen is less than the skeleton void ratio of the coarse aggregate, the mineral void ratio of the VVTM specimen is ≥14.5 and the specimen void ratio is 2.5-4;
[0015] When the first specimen, the second specimen and the third specimen do not simultaneously meet the design standard of the vertical vibration compaction method, the grading boundary values of the first graded coarse aggregate and the second graded coarse aggregate are reduced, and steps (2) to (7) are repeated until the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, and the asphalt-stone ratio of the specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen is selected as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture.
[0016] Preferably, in the step (3), the relationship between the volume ratio of the coarse aggregate, the fine aggregate and the asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of the asphalt mortar in the volume of mastic is as shown in Formula 1:
[0017] V 粗 :V 细 :V 胶浆 =1-VCA DRC :a(1-b)VCA DRC :abVCA DRC Formula 1
[0018] In formula 1, V 粗 is the volume of coarse aggregate, V 细 is the volume of fine aggregate, V 胶浆 is the volume of asphalt mortar, VCA DRC is the skeleton gap ratio of coarse aggregate; a is the ratio of mastic volume to the skeleton gap ratio of coarse aggregate, and b is the volume percentage of asphalt mortar in mastic volume.
[0019] Preferably, in step (4), the relationship between the apparent relative density of the mineral powder, the specific gravity of the fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the ratio of the volume percentage of asphalt mortar in the volume of mastic to the volume percentage of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is as shown in Formula 2:
[0020]
[0021] In formula 2, A is the volume percentage of coarse aggregate, B is the volume percentage of fine aggregate, C is the volume percentage of mineral powder, D is the volume percentage of asphalt, and E is the volume percentage of fiber; ρ 矿 is the apparent relative density of mineral powder, ρ 纤 is the specific gravity of the fiber, ρ 沥 is the density of asphalt.
[0022] Preferably, in the step (5), the calculation formula for the sieve pass rate of 4.75mm grade ore material is shown in Formula 3; the calculation formula for the sieve pass rate of 0.075 grade ore material is shown in Formula 4; the calculation formula for the sieve pass rate of 9.5mm grade ore material is shown in Formula 5; the calculation formula for the sieve pass rate of 2.36mm grade ore material is shown in Formula 6; the calculation formula for the sieve pass rate of 1.18mm grade ore material is shown in Formula 7; the calculation formula for the sieve pass rate of 0.6mm grade ore material is shown in Formula 8; the calculation formula for the sieve pass rate of 0.3mm grade ore material is shown in Formula 9; the calculation formula for the sieve pass rate of 0.15mm grade ore material is shown in Formula 10;
[0023]
[0024]
[0025] 100-k(100-P 4.75 ) Formula 5;
[0026] 0.7×(P 4.75 -P 0.075 )+P 0.075 Formula 6;
[0027] 0.7 2 ×(P 4.75 -P 0.075 )+P 0.075 Formula 7;
[0028] 0.7 3 ×(P 4.75 -P 0.075 )+P 0.075 Formula 8;
[0029] 0.7 4 ×(P4.75 -P 0.075 )+P 0.075 Formula 9;
[0030] 0.7 5 ×(P 4.75 -P 0.075 )+P 0.075 Formula 10;
[0031] In equations 3 and 4, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder;
[0032] In formula 5, k is the mass percentage of the first graded coarse aggregate in the coarse aggregate, P 4.75 The passing rate of 4.75mm sieve hole for mineral materials;
[0033] In formulas 6 to 10, P 0.075 It is the passing rate of 0.075mm sieve hole for mineral materials.
[0034] Preferably, in the step (5), after obtaining the sieve pass rate of each grade of mineral materials of the recommended grading, the method further includes: obtaining a sieve pass rate range of each grade of mineral materials of the recommended grading that meets the construction specifications based on the sieve pass rate of each grade of mineral materials of the recommended grading, and obtaining a sieve pass rate of each grade of mineral materials of the synthetic grading that is closest to the sieve pass rate of each grade of mineral materials of the recommended grading based on the sieve pass rate range of each grade of mineral materials of the recommended grading that meets the construction specifications; in the step (6), when the VVTM specimen is prepared by the vertical vibration compaction method, it is carried out according to the initial oil-stone ratio and the sieve pass rate of each grade of mineral materials of the synthetic grading.
[0035] Preferably, in step (6), the calculation formula of the initial asphalt-stone ratio is as shown in Formula 11:
[0036]
[0037] In formula 11, Dγ b is the density of asphalt, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder.
[0038] Preferably, in step (6), the calculation formula of the fiber content is as shown in Formula 12:
[0039]
[0040] In formula 12, Eγ x is the specific gravity of the fiber, Aγ cis the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder.
[0041] Preferably, in step (7), the physical parameters of the VVTM specimen also include one or more of asphalt saturation, Marshall stability and flow value; the vertical vibration compaction method design standard also includes: the asphalt saturation is 75-85%, the Marshall stability is ≥10kN and the flow value is 1.5-4mm. One or more.
[0042] Preferably, in step (2), the skeleton gap ratio of the coarse aggregate is calculated according to the "Highway Engineering Aggregate Test Procedure" T309-2005;
[0043] In step (7), the gross volume density of the VVTM specimen is determined according to the "Highway Engineering Aggregate Test Procedure" T309-2005.
[0044] Preferably, after step (7), the method further includes: designing an SMA-13 asphalt mixture according to the VVTM volume design method of steps (1) to (7), preparing an SMA-13 asphalt mixture sample by a vertical vibration compaction method, and testing the performance of the SMA-13 asphalt mixture sample; when the SMA-13 asphalt mixture sample does not meet the requirements of the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering", replacing one or more of asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose, re-designing the SMA-13 asphalt mixture according to the VVTM volume design method of steps (1) to (7), preparing an SMA-13 asphalt mixture sample by a vertical vibration compaction method, and testing the performance of the SMA-13 asphalt mixture sample; until the performance of the SMA-13 asphalt mixture sample meets the requirements of the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering";
[0045] The performance of the SMA-13 asphalt mixture sample includes at least one of high temperature stability, low temperature mechanical properties, water stability, leakage performance and scattering performance.
[0046] The present invention provides a SMA-13 asphalt mixture VVTM volume design method. The present invention adopts a volume design method based on vibration compaction (VVTM) to design the mix proportion of SMA-13 asphalt mixture, including the determination of physical parameters of SMA-13 asphalt mixture, the design of mineral gradation, and the determination of the optimal oil-stone ratio. The results of the embodiments show that the SMA-13 asphalt mixture designed by the design method provided by the present invention has good road performance, low asphalt dosage and simple operation. Compared with the Marshall method, the vibration molding method can greatly improve the high temperature performance and water stability of the SMA-13 mixture, and the low temperature deformation capacity is only slightly reduced; at the same time, the volume design mix ratio method can further improve the high temperature performance and water stability of the vibration molded specimen and improve the low temperature deformation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The synthetic gradation curve diagram provided by Example 1 of the present invention;
[0048] Figure 2 This is a curve showing the variation of the asphalt-stone ratio with the apparent relative density of fine aggregate in Example 1 of the present invention;
[0049] Figure 3 The curve of Marshall stability versus asphalt-stone ratio in Example 1 of the present invention;
[0050] Figure 4 The curve of porosity changing with asphalt-stone ratio in Example 1 of the present invention;
[0051] Figure 5 The curve of asphalt saturation changing with asphalt-stone ratio in Example 1 of the present invention;
[0052] Figure 6 This is the curve of vertical vibration design standard changing with the oilstone ratio in Example 1 of the present invention. DETAILED DESCRIPTION
[0053] The present invention provides a SMA-13 asphalt mixture VVTM volume design method, wherein the SMA-13 asphalt mixture comprises asphalt, coarse aggregate, fine aggregate, mineral powder and fiber; mastic comprises asphalt, fine aggregate, mineral powder and fiber; asphalt mortar comprises asphalt, mineral powder and fiber; and the method comprises the following steps:
[0054] (1) obtaining physical parameters of the asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose, wherein the physical parameters include the density of asphalt, the apparent relative density and the bulk relative density of the coarse aggregate, the apparent relative density of the fine aggregate, the apparent relative density of the mineral powder, and the specific gravity of the fiber;
[0055] (2) The coarse aggregate includes a first-graded coarse aggregate and a second-graded coarse aggregate. According to the relationship between the skeleton gap ratio of the coarse aggregate and the mass percentage of the first-graded coarse aggregate in the coarse aggregate, within the mass percentage range of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the second-graded coarse aggregate in the coarse aggregate and the skeleton gap ratio of the coarse aggregate are obtained based on the principle that the value of the skeleton gap ratio of the coarse aggregate is relatively minimum; the particle size of the first-graded coarse aggregate is 9.5 to 16 mm, and the particle size of the second-graded coarse aggregate is 4.75 to 9.5 mm;
[0056] (3) According to the relationship between the mechanical properties of the SMA-13 asphalt mixture and the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture, and the relationship between the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of asphalt mortar in the volume of mastic, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate and the volume percentage of asphalt mortar in the volume of mastic are obtained based on the principle of optimizing the mechanical properties of the SMA-13 asphalt mixture; the mechanical properties of the SMA-13 asphalt mixture include one or more of Marshall stability, compressive strength, shear strength and splitting strength;
[0057] (4) according to the relationship between the apparent relative density of mineral powder, the specific gravity of fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the volume percentage of asphalt mortar in the volume of mastic, the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is obtained;
[0058] (5) According to the apparent relative density of the mineral powder, the apparent relative density of the coarse aggregate and the apparent relative density of the fine aggregate, the sieve hole pass rate of the key-grade mineral material is obtained, and the sieve hole pass rate of the key-grade mineral material includes the sieve hole pass rate of the 4.75mm grade mineral material and the sieve hole pass rate of the 0.075 grade mineral material; according to the mass percentage of the first graded coarse aggregate and the sieve hole pass rate of the 4.75mm grade mineral material, the sieve hole pass rate of the 9.5mm grade mineral material is obtained; the sieve hole pass rate of the 16mm grade mineral material is 100%; according to the sieve hole pass rate of the key-grade mineral material, the sieve hole pass rate of the 9.5mm grade mineral material and the sieve hole pass rate of the 16mm grade mineral material, Obtain the remaining recommended gradation sieve hole pass rate of each grade of ore material; the recommended gradation sieve hole pass rate of each grade of ore material includes: 16mm grade ore sieve hole pass rate, 9.5mm grade ore sieve hole pass rate, 4.75mm grade ore sieve hole pass rate, 0.075 grade ore sieve hole pass rate and the remaining recommended gradation sieve hole pass rate of each grade of ore material; the remaining recommended gradation sieve hole pass rate of each grade of ore material includes: 2.36mm grade ore sieve hole pass rate, 1.18mm grade ore sieve hole pass rate, 0.6mm grade ore sieve hole pass rate, 0.3mm grade ore sieve hole pass rate and 0.15 grade ore sieve hole pass rate;
[0059] There is no time sequence restriction between steps (2) to (4) and step (5);
[0060] (6) obtaining an initial oil-to-stone ratio according to the density of asphalt, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; obtaining a fiber content according to the specific gravity of fiber, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; preparing a VVTM specimen by a vertical vibration compaction method according to the initial oil-to-stone ratio, the sieve pass rate of each grade of mineral material of the recommended gradation, and the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder, and fiber in the SMA-13 asphalt mixture; the VVTM specimen includes a first specimen, a second specimen, and a third specimen, the oil-to-stone ratio of the first specimen being 0.2 to 0.4 less than the initial oil-to-stone ratio; the oil-to-stone ratio of the second specimen being the initial oil-to-stone ratio; and the oil-to-stone ratio of the third specimen being 0.2 to 0.4 greater than the initial oil-to-stone ratio;
[0061] (7) determining the gross volume density of the VVTM specimen, and obtaining the physical parameters of the VVTM specimen according to the gross volume density, wherein the physical parameters of the VVTM specimen include the coarse aggregate void ratio, the mineral void ratio and the specimen void ratio; when the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, selecting the oil-stone ratio of the VVTM specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen as the optimal oil-stone ratio of the SMA-13 asphalt mixture; the design standard of the vertical vibration compaction method includes: the coarse aggregate void ratio of the VVTM specimen is less than the skeleton void ratio of the coarse aggregate, the mineral void ratio of the VVTM specimen is ≥14.5 and the specimen void ratio is 2.5-4;
[0062] When the first specimen, the second specimen and the third specimen do not simultaneously meet the design standard of the vertical vibration compaction method, the grading boundary values of the first graded coarse aggregate and the second graded coarse aggregate are reduced, and steps (2) to (7) are repeated until the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, and the asphalt-stone ratio of the specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen is selected as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture.
[0063] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0064] The present invention obtains the physical parameters of the asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose, and the physical parameters include the density of asphalt, the apparent relative density and bulk relative density of coarse aggregate, the apparent relative density of fine aggregate, the apparent relative density of mineral powder, and the specific gravity of fiber.
[0065] The present invention preferably selects representative samples of asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose according to the actual materials used in the project, and measures the technical indicators of the asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose.
[0066] In the present invention, the technical indicators are the physical parameters of asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose.
[0067] In the present invention, the physical parameters of the asphalt include the density of the asphalt (g / cm 3 ), the density of the asphalt is preferably the density at 15°C. In the present invention, the physical parameters of the asphalt preferably also include: 25°C needle penetration (0.1mm), 5°C elongation (cm), softening point (ring and ball method) (°C), and RTFOT residue. The RTFOT residue preferably includes: mass loss (%), needle penetration ratio (%) and 5°C elongation (cm).
[0068] In the present invention, the physical parameters of the coarse aggregate include the apparent relative density (g / cm 3 ) and gross volume relative density (g / cm 3 ). In the present invention, the physical parameters of the coarse aggregate preferably also include: water absorption (%), soft stone content (%), crushing value (%), Los Angeles abrasion loss (%) and needle-like content (%). The needle-like content (%) preferably includes: needle-like content (%)>9.5mm and needle-like content (%)<9.5mm.
[0069] In the present invention, the physical parameters of the fine aggregate include apparent relative density (g / cm 3 In the present invention, the physical parameters of the fine aggregate preferably also include: sand equivalent (%), methylene blue value (g / kg) and angularity (s).
[0070] In the present invention, the physical parameters of the mineral powder include the apparent relative density (g / cm 3 In the present invention, the physical parameters of the mineral powder preferably also include: water content (%), hydrophilic coefficient, plasticity index (I P ) and heating stability.
[0071] In the present invention, the physical parameters of the fiber include specific gravity (g / cm 3 ). In the present invention, the physical parameters of the fiber preferably also include: average length (mm), fiber diameter (mm), melting point (°C), moisture absorption rate (%), tensile strength (MPa), elastic modulus (GPa) and elongation at break (%).
[0072] In the present invention, the physical parameters of asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose preferably all meet the technical requirements of JTGF40-2004.
[0073] In the present invention, the coarse aggregate includes first-graded coarse aggregate and second-graded coarse aggregate. According to the relationship between the skeleton gap ratio of the coarse aggregate and the mass percentage of the first-graded coarse aggregate in the coarse aggregate, within the mass percentage range of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the second-graded coarse aggregate in the coarse aggregate and the skeleton gap ratio of the coarse aggregate are obtained on the principle of taking the relatively minimum value of the skeleton gap ratio of the coarse aggregate within the mass percentage range of the first-graded coarse aggregate in the coarse aggregate. The particle size of the first-graded coarse aggregate is 9.5-16 mm, and the particle size of the second-graded coarse aggregate is 4.75-9.5 mm.
[0074] In the present invention, the mass percentage range of the first graded coarse aggregate in the coarse aggregate is determined based on engineering experience.
[0075] The present invention preferably calculates the skeleton void ratio (VCA) of the coarse aggregate according to the "Highway Engineering Aggregate Test Regulations" T309-2005. DRC ).
[0076] In the present invention, the calculation formula of the skeleton void ratio of the coarse aggregate is preferably as shown in Formula 13:
[0077]
[0078] In formula 13, ρ s is the relative density of the coarse aggregate skeleton after compaction; ρ ca It is the relative bulk density of coarse aggregate.
[0079] In the present invention, the particle size of the first graded coarse aggregate is 9.5 to 16 mm, preferably 9.5 to 13.2 mm. The particle size of the second graded coarse aggregate is 4.75 to 9.5 mm, preferably 4.75 to 9.5 mm.
[0080] In a specific embodiment of the present invention, the mass percentage of the first graded coarse aggregate is preferably in the range of 55-65%; the mass percentage of the second graded coarse aggregate is preferably in the range of 35-45%.
[0081] In the present invention, the mass percentage of the first-graded coarse aggregate in the coarse aggregate is preferably 0.6, the mass percentage of the second-graded coarse aggregate in the coarse aggregate is preferably 0.4, and the skeleton gap ratio of the coarse aggregate is preferably 41.1.
[0082] According to the relationship between the mechanical properties of the SMA-13 asphalt mixture and the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture, and the relationship between the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the mastic volume, and the volume percentage of the asphalt mortar in the mastic volume, the ratio of the mastic volume to the skeleton gap ratio of the coarse aggregate and the volume percentage of the asphalt mortar in the mastic volume are obtained based on the principle of optimizing the mechanical properties of the SMA-13 asphalt mixture; the mechanical properties of the SMA-13 asphalt mixture include one or more of Marshall stability, compressive strength, shear strength and splitting strength.
[0083] In the present invention, the relationship between the volume ratio of the coarse aggregate, the fine aggregate and the asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of the asphalt mortar in the volume of mastic is as shown in Formula 1:
[0084] V 粗 :V 细 :V胶浆 =1-VCA DRC :a(1-b)VCA DRC :abVCA DRC Formula 1
[0085] In formula 1, V 粗 is the volume of coarse aggregate, V 细 is the volume of fine aggregate, V 胶浆 is the volume of asphalt mortar, VCA DRC is the skeleton gap ratio of coarse aggregate; a is the ratio of mastic volume to the skeleton gap ratio of coarse aggregate, and b is the volume percentage of asphalt mortar in mastic volume.
[0086] In the present invention, when the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate is preferably 0.85, the mechanical properties of the SMA-13 asphalt mixture are optimal, and the volume percentage of asphalt mortar in the volume of mastic is preferably 0.59.
[0087] In the present invention, when the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate is preferably 0.85 and the volume percentage of asphalt mortar in the volume of mastic is preferably 0.59, the relationship between the volume percentages of coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture is preferably as shown in Formula 1-1:
[0088] V 粗 :V 细 :V 胶浆 =1-VCA DRC :0.35VCA DRC :0.5VCA DRC Formula 1-1.
[0089] The present invention obtains the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture according to the relationship between the apparent relative density of mineral powder, the specific gravity of fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap rate of the coarse aggregate and the volume percentage of asphalt mortar in the volume of mastic.
[0090] In the present invention, the relationship between the apparent relative density of the mineral powder, the specific gravity of the fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the ratio of the volume percentage of asphalt mortar in the volume of mastic to the volume percentage of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is as shown in Formula 2:
[0091]
[0092] In formula 2, A is the volume percentage of coarse aggregate, B is the volume percentage of fine aggregate, C is the volume percentage of mineral powder, D is the volume percentage of asphalt, and E is the volume percentage of fiber; ρ 矿 is the apparent relative density of mineral powder, ρ 纤 is the specific gravity of the fiber, ρ 沥 is the density of asphalt.
[0093] In the present invention, the skeleton gap ratio of the coarse aggregate is preferably 41.1, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate is preferably 0.85, the volume percentage of asphalt mortar in the volume of mastic is preferably 0.59, and the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is preferably 58.9:14.4:7.4:12.3:0.8.
[0094] The invention obtains the key-grade ore sieve hole pass rate according to the apparent relative density of the ore powder, the apparent relative density of the coarse aggregate and the apparent relative density of the fine aggregate, wherein the key-grade ore sieve hole pass rate includes the 4.75mm grade ore sieve hole pass rate and the 0.075 grade ore sieve hole pass rate; the 9.5mm grade ore sieve hole pass rate is obtained according to the mass percentage of the first graded coarse aggregate and the 4.75mm grade ore sieve hole pass rate; the 16mm grade ore sieve hole pass rate is 100%; according to the key-grade ore sieve hole pass rate, the 9.5mm grade ore sieve hole pass rate and the 16mm grade ore sieve hole pass rate, the The remaining recommended grading sieve hole pass rates of each grade of ore materials are obtained; the recommended grading sieve hole pass rates of each grade of ore materials include: 16mm grade ore hole pass rate, 9.5mm grade ore hole pass rate, 4.75mm grade ore hole pass rate, 0.075 grade ore hole pass rate and the remaining recommended grading sieve hole pass rates of each grade of ore materials; the remaining recommended grading sieve hole pass rates of each grade of ore materials include: 2.36mm grade ore hole pass rate, 1.18mm grade ore hole pass rate, 0.6mm grade ore hole pass rate, 0.3mm grade ore hole pass rate and 0.15 grade ore hole pass rate.
[0095] In the present invention, the calculation formula of the sieve hole pass rate of 4.75mm grade ore material is shown in Formula 3; the calculation formula of the sieve hole pass rate of 0.075 grade ore material is shown in Formula 4; the calculation formula of the sieve hole pass rate of 9.5mm grade ore material is shown in Formula 5; the calculation formula of the sieve hole pass rate of 2.36mm grade ore material is shown in Formula 6; the calculation formula of the sieve hole pass rate of 1.18mm grade ore material is shown in Formula 7; the calculation formula of the sieve hole pass rate of 0.6mm grade ore material is shown in Formula 8; the calculation formula of the sieve hole pass rate of 0.3mm grade ore material is shown in Formula 9; the calculation formula of the sieve hole pass rate of 0.15mm is shown in Formula 10;
[0096]
[0097]
[0098] 100-k(100-P 4.75 ) Formula 5;
[0099] 0.7×(P 4.75 -P 0.075 )+P 0.075 Formula 6;
[0100] 0.7 2 ×(P 4.75 -P 0.075 )+P 0.075 Formula 7;
[0101] 0.7 3 ×(P 4.75 -P 0.075 )+P 0.075 Formula 8;
[0102] 0.7 4 ×(P 4.75 -P 0.075 )+P 0.075 Formula 9;
[0103] 0.7 5 ×(P 4.75 -P 0.075 )+P 0.075 Formula 10;
[0104] In equations 3 and 4, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder;
[0105] In formula 5, k is the mass percentage of the first graded coarse aggregate in the coarse aggregate, P 4.75 The passing rate of 4.75mm sieve hole for mineral materials;
[0106] In formulas 6 to 10, P 0.075 It is the passing rate of 0.075mm sieve hole for mineral materials.
[0107] In the present invention, the 16mm-grade ore material sieve aperture pass rate grade is preferably replaced by the 13.2mm-grade ore material sieve aperture pass rate grade.
[0108] In a specific embodiment of the present invention, the calculation table of the sieve pass rate of each retaining material of the recommended gradation is preferably as shown in Table 1:
[0109] Table 1 Calculation table of sieve pass rate of each ore retaining material with recommended gradation
[0110]
[0111]
[0112] In the present invention, after obtaining the sieve pass rate of each grade of mineral materials in the recommended grading, the present invention preferably further includes: obtaining a sieve pass rate range of each grade of mineral materials in the recommended grading that meets the construction specifications based on the sieve pass rate of each grade of mineral materials in the recommended grading, as shown in Table 1; obtaining a sieve pass rate of each grade of mineral materials in the synthetic grading that is closest to the sieve pass rate of each grade of mineral materials in the recommended grading that meets the construction specifications; the present invention preferably adopts the vertical vibration compaction method to make VVTM specimens, based on the initial oil-stone ratio and the sieve pass rate of each grade of mineral materials in the synthetic grading.
[0113] In the present invention, the range of sieve pass rate of each grade of the recommended grading mineral material that meets the construction specifications is determined based on engineering experience.
[0114] In a specific embodiment of the present invention, the present invention adjusts the proportion of each grade of mineral material according to the calculated recommended gradation to obtain a composite gradation and gradation curve that meets the recommended gradation range of the construction technical specification and is closest to the recommended gradation.
[0115] The present invention obtains an initial oil-to-stone ratio according to the density of asphalt, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate and the apparent relative density of fine aggregate; obtains the fiber content according to the specific gravity of fiber, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate and the apparent relative density of fine aggregate; adopts a vertical vibration compaction method to prepare a VVTM specimen according to the initial oil-to-stone ratio, the sieve pass rate of each grade of mineral material of the recommended gradation and the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture; the VVTM specimen includes a first specimen, a second specimen and a third specimen, the oil-to-stone ratio of the first specimen is 0.2 to 0.4 less than the initial oil-to-stone ratio; the oil-to-stone ratio of the second specimen is the initial oil-to-stone ratio; the oil-to-stone ratio of the third specimen is 0.2 to 0.4 greater than the initial oil-to-stone ratio.
[0116] In the present invention, the calculation formula of the initial asphalt-stone ratio is preferably as shown in Formula 11:
[0117]
[0118] In formula 11, Dγ b is the density of asphalt, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder.
[0119] In the present invention, the calculation formula of the fiber content is preferably as shown in Formula 12:
[0120]
[0121] In formula 12, Eγ x is the specific gravity of the fiber, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder.
[0122] The present invention measures the gross volume density of the VVTM specimen, and obtains the physical parameters of the VVTM specimen according to the gross volume density. The physical parameters of the VVTM specimen include the coarse aggregate void ratio (VCA) and the mix ), aggregate void ratio (VMA) and specimen void ratio (VV); when the first specimen, the second specimen and the third specimen simultaneously meet the design criteria of the vertical vibration compaction method, the asphalt-stone ratio of the VVTM specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen is selected as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture; the design criteria of the vertical vibration compaction method include: the coarse aggregate void ratio (VCA) of the VVTM specimen mix )<the skeleton void ratio of coarse aggregate (VCA DRC ), the VVTM specimen’s mineral material void ratio (VMA) is ≥14.5 and the specimen void ratio (VV) is 2.5-4;
[0123] When the first specimen, the second specimen and the third specimen do not simultaneously meet the design standard of the vertical vibration compaction method, the grading boundary values of the first graded coarse aggregate and the second graded coarse aggregate are reduced, and steps (2) to (7) are repeated until the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, and the asphalt-stone ratio of the specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen is selected as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture.
[0124] In the present invention, the target porosity is a design preset value of the SMA-13 asphalt mixture.
[0125] In the present invention, the physical parameters of the VVTM specimen also include one or more of asphalt saturation (VFA), Marshall stability (MS) and flow value (FL); the vertical vibration compaction method design standard also includes: the asphalt saturation is 75-85%, the Marshall stability is ≥10kN and the flow value is 1.5-4mm. One or more.
[0126] The present invention preferably determines the gross volume density of the VVTM specimen according to the "Highway Engineering Aggregate Test Procedure" T309-2005.
[0127] In a specific embodiment of the present invention, the present invention preferably calculates VCA by testing the bulk density of the piece by water weight method. mix , VMA and VV.
[0128] In the present invention, the number of the first test pieces is preferably ≥4-6; the number of the second test pieces is preferably ≥4-6; and the number of the third test pieces is preferably ≥4-6.
[0129] In the present invention, the size of the first test piece is preferably Φ100 mm×h63.5 mm; the size of the second test piece is preferably Φ100 mm×h63.5 mm; the size of the third test piece is preferably Φ100 mm×h63.5 mm.
[0130] In a specific embodiment of the present invention, the design standard of the vertical vibration compaction method is preferably as shown in Table 2:
[0131] Table 2 Design standards for vertical vibration compaction of SMA-13 asphalt mixture
[0132] Specimen size (mm) VV(%) VFA(%) VMA(%) MS(KN) FL(mm) Φ100×h63.5 2.5~4.0 75~85 ≥14.5 ≥10 1.5~4.0
[0133] In the present invention, the present invention preferably further comprises: testing the performance of the SMA-13 asphalt mixture designed according to the above steps; when the SMA-13 asphalt mixture does not meet the requirements of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", replacing one or more of asphalt, coarse aggregate, fine aggregate, mineral powder and cellulose, and re-designing the SMA-13 asphalt mixture according to the above steps until the performance of the designed SMA-13 asphalt mixture meets the requirements of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering";
[0134] The performance of the SMA-13 asphalt mixture includes one or more of high temperature stability, low temperature mechanical properties, water stability, leakage performance and scattering performance.
[0135] The present invention provides a SMA-13 asphalt mixture VVTM volume design method. The present invention adopts a volume design method based on vibration compaction (VVTM) to design the mix proportion of SMA-13 asphalt mixture, including the determination of physical parameters of SMA-13 asphalt mixture, the design of mineral gradation, and the determination of the optimal oil-stone ratio. The results of the embodiments show that the SMA-13 asphalt mixture designed by the design method provided by the present invention has good road performance, low asphalt dosage and simple operation. Compared with the Marshall method, the vibration molding method can greatly improve the high temperature performance and water stability of the SMA-13 mixture, and the low temperature deformation capacity is only slightly reduced; at the same time, the volume design mix ratio method can further improve the high temperature performance and water stability of the vibration molded specimen and improve the low temperature deformation resistance.
[0136] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0137] Example 1
[0138] See also Figures 2 to 5 This embodiment provides a SMA-13 asphalt mixture VVTM volume design method, which uses a volume design method based on vibration compaction (VVTM) to perform mix design, specifically following the following steps:
[0139] 1. Material selection and testing
[0140] The materials used are SBS modified asphalt from Ssangyong, South Korea, basalt from Linxian County, Shanxi Province, machine-made sand from limestone produced in Shangluo, Shaanxi Province, mineral powder from limestone produced in Liulin Stone Factory, Shanxi Province, and lignin fiber provided by a company in Jiangsu Province. The test results of its technical properties are shown in Tables 3 to 7.
[0141] Table 3 Technical properties of asphalt
[0142]
[0143] Table 4 Technical indicators of coarse aggregate
[0144]
[0145] Table 5 Technical indicators of fine aggregate
[0146] Test Project Specified value Measured value Apparent relative density ≥2.5 2.732 Sand equivalent (%) ≥70 72 Methylene blue value (g / kg) ≤25 10.0 Angularity(s) ≥30 33.2
[0147] Table 6 Technical properties of mineral powder
[0148] Test Project Specified value Measured value Apparent relative density ≥2.5 2.682 Water content (%) ≤1 0.9 Hydrophilicity <1 0.82 <![CDATA[Plasticity index (I P )]]> 3.1 <4 Heating stability Measured records There is no obvious change before and after heating, meeting the construction requirements
[0149] Table 7 Fiber technical properties
[0150]
[0151] After testing, all technical indicators of raw materials meet the technical requirements of JTG F40-2004.
[0152] 2. Design of mineral material gradation
[0153] (1) Coarse aggregate gradation and VCA DRC Determination
[0154] According to the "Highway Engineering Aggregate Test Procedure", the VCA of coarse aggregate 9.5-16mm:4.75-9.5mm mass ratios was 55:45, 60:40 and 65:35 respectively. DRC , the test results are shown in Table 8.
[0155] Table 8 VCA DRC Test Results
[0156] 9.5~13.2mm:4.75~9.5mm 55:45 60:40 65:35 <![CDATA[VCA DRC Average value of]]> 41.4 41.1 41.3
[0157] When the mass ratio of aggregate 9.5~13.2mm:4.75~9.5mm is 60:40, VCA DRC Relatively speaking, the smallest size, so the proportion of 9.5-13.2 mm aggregate in coarse aggregate is 0.6.
[0158] (2) Calculation of volume ratio of each component material
[0159] Mastic volume and VCA DRC When the ratio a=0.85, the mechanical properties of SMA-13 asphalt mixture are the best, and the ratio of asphalt mortar in mastic volume is b=0.59. According to the optimal volume ratio of coarse aggregate, fine aggregate and asphalt mortar in the volume design composition of SMA-13 mixture, equation 1, substituting a=0.85 and b=0.59, the optimal volume composition ratio V of SMA-13 mixture is obtained. 粗 :V 细 :V 胶浆 =1-VCA DRC :0.35VCA DRC :0.5VCA DRC .
[0160] The volume ratios of SMA-13 coarse aggregate (A), fine aggregate (B), mineral powder (C), asphalt (D), and fiber (E) are calculated according to Formula 2. The calculation results are shown in Table 9.
[0161] Table 9 Volume ratio parameter calculation results
[0162]
[0163] (3) Conversion of ore grade
[0164] Calculate the passing rate of each grade of recommended ore, and the results are shown in Table 10.
[0165] Table 10 Recommended grading pass rate of each grade of ore
[0166] Sieve hole diameter (mm) 13.2 9.5 4.75 2.36 1.18 0.6 0.3 0.5 0.075 Passing mass percentage (%) 100 55.4 25.7 20.1 16.6 14.2 12.5 11.4 8.6
[0167] (4) Calculation of initial oil-stone ratio
[0168]
[0169] (5) Calculation of fiber content
[0170]
[0171] (6) Determination of composite gradation curve
[0172] According to the calculated recommended gradation, the proportion of each grade of ore is adjusted to obtain the synthetic gradation and gradation curve that meets the recommended gradation range of the construction technical specifications and is closest to the recommended gradation. See Table 11 and Figure 1 .
[0173] Table 11 SMA-13 asphalt mixture mineral material screening results
[0174]
[0175]
[0176] 3. Determination of the optimal oil-stone ratio
[0177] (1) Estimate the initial oil-rock ratio P based on engineering experience a0 =5.3%, and VVTM was used to make three groups of asphalt mixture specimens with asphalt-to-stone ratios of 5.0%, 5.3%, and 5.6%, respectively, with 6 specimens in each group.
[0178] (2) Determine the VV, VMA, VFA, and VCA of the molded specimens according to the requirements of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) mix , MS and FL. The test results are shown in Table 12.
[0179] Table 12 Technical standards for vertical vibration of SMA-13 asphalt mixture
[0180]
[0181] (3) When the oil-stone ratio is 5.3%, all indicators meet the requirements.
[0182] 4. Performance inspection
[0183] The rutting plate time and VVTM specimens were made according to the optimal oil-stone ratio of 5.3% determined in step 3. The test results are shown in Table 13.
[0184] Table 13 Performance test results of SMA-13 asphalt mixture
[0185]
[0186] The test results show that all the tests meet the engineering requirements.
[0187] The SMA-13 asphalt mixture VVTM volume design method provided by the present invention is compared with the Marshall method design method. The design results of different types of SMA-13 mixture proportions designed using the VVTM volume design method and the Marshall method are shown in Table 14. In Table 14, the test results are expressed in G M , G S and G V The points represent the Marshall specimen (double-sided compaction 75 times), SGC specimen (rotational compaction 100 times) and VVTM specimen (vibration compaction 65s) when the standard median gradation is adopted. V Represents the VVTM specimen obtained by the volume design method (vibration compaction 65s).
[0188] Table 14 Comparison of SMA-13 mixture proportion design results with different gradations
[0189]
[0190] Table 14 shows that when the SMA-13 mixture gradation is the same, the optimal asphalt-stone ratio of the mixtures with different compaction methods is basically the same after the compaction standard is improved. When vibration forming specimens are used, the optimal asphalt-stone ratio of the mixture designed by the volume method is lower than that of the mixture using the median value of the standard gradation, and the density is higher.
[0191] The road performance test results and comparison results of different types of SMA-13 mixtures designed by VVTM volume design method and Marshall method are shown in Table 15 and Table 16, where Marshall stability, dynamic stability, shear strength and splitting strength are expressed as MS, DS, τ d , Ri, the immersion Marshall stability and freeze-thaw splitting strength ratio are represented by MS0 and TSR respectively.
[0192] Table 15 Test results of road performance of various types of SMA-13 mixtures
[0193]
[0194]
[0195] Table 16 Comparison of road performance of various types of SMA-13 mixtures
[0196]
[0197] It can be seen from Tables 15 and 16 that when the median gradation of the specification is adopted, the Marshall stability, dynamic stability, shear strength and splitting strength of the VVTM specimen are greatly improved compared with the Marshall specimen, which are increased by about 36%, 29%, 39% and 32% respectively, the water-immersed Marshall stability and freeze-thaw splitting strength ratio are increased by 4%, and the low-temperature bending strain is reduced by 4%. Compared with the Marshall specimen with the median gradation of the specification, the Marshall stability, dynamic stability, shear strength and splitting strength of the VVTM specimen designed by the volume method can be improved by about 61%, 49%, 57% and 41%, respectively, the water stability performance is improved by 6%, and the low-temperature bending strain is slightly reduced. Compared with the SGC specimen with the median gradation of the specification, the Marshall stability, dynamic stability, shear strength, splitting strength, water-immersed Marshall and residual strength ratio can be improved by about 21%, 24%, 9%, 14%, 4% and 4%, respectively, and the low-temperature bending strain is reduced by 4%. Compared with the VVTM specimens with the median grade in the specification, the VVTM specimens designed by the volume method can improve the Marshall stability, dynamic stability, shear strength, splitting strength, water-immersed Marshall, residual strength ratio and low-temperature bending strain by about 18%, 15%, 13%, 7%, 1%, 2% and 3% respectively. According to the test results, the vibration molding method can greatly improve the high-temperature performance and water stability of SMA-13 mixture, but the low-temperature deformation capacity is slightly reduced; the volume design mix ratio method can further improve the high-temperature performance and water stability of the vibration molding specimens and improve the low-temperature deformation resistance.
[0198] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A VVTM volume design method for SMA-13 asphalt mixture, wherein the SMA-13 asphalt mixture comprises asphalt, coarse aggregate, fine aggregate, mineral powder and fiber; mastic comprises asphalt, fine aggregate, mineral powder and fiber; asphalt mortar comprises asphalt, mineral powder and fiber; characterized in that: The following steps are involved: (1) obtaining physical parameters of the asphalt, coarse aggregate, fine aggregate, mineral powder and fiber, wherein the physical parameters include density of asphalt, apparent relative density and bulk relative density of coarse aggregate, apparent relative density of fine aggregate, apparent relative density of mineral powder and specific gravity of fiber; (2) The coarse aggregate includes a first-graded coarse aggregate and a second-graded coarse aggregate. According to the relationship between the skeleton gap ratio of the coarse aggregate and the mass percentage of the first-graded coarse aggregate in the coarse aggregate, within the mass percentage range of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the first-graded coarse aggregate in the coarse aggregate, the mass percentage of the second-graded coarse aggregate in the coarse aggregate and the skeleton gap ratio of the coarse aggregate are obtained based on the principle that the skeleton gap ratio of the coarse aggregate is relatively minimum; the particle size of the first-graded coarse aggregate is 9.5-16 mm, and the particle size of the second-graded coarse aggregate is 4.75-9.5 mm; in step (2), the skeleton gap ratio of the coarse aggregate is calculated according to the Test Procedure for Aggregates for Highway Engineering T309-2005; (3) According to the relationship between the mechanical properties of the SMA-13 asphalt mixture and the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture, and the relationship between the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of asphalt mortar in the volume of mastic, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate and the volume percentage of asphalt mortar in the volume of mastic are obtained based on the principle of optimizing the mechanical properties of the SMA-13 asphalt mixture; the mechanical properties of the SMA-13 asphalt mixture include one or more of Marshall stability, compressive strength, shear strength and splitting strength; in the step (3), the relationship between the volume ratio of the coarse aggregate, fine aggregate and asphalt mortar in the SMA-13 asphalt mixture and the skeleton gap ratio of the coarse aggregate, the volume of mastic, and the volume percentage of asphalt mortar in the volume of mastic is as shown in Formula 1: V 粗 : V 细 : V 胶浆 = 1 - VCA DRC : a(1 - b)VCA DRC : abVCA DRC Equation 1; In formula 1, V 粗 is the volume of coarse aggregate, V 细 is the volume of fine aggregate, V 胶浆 is the volume of asphalt mortar, VCA DRC is the skeleton gap ratio of the coarse aggregate; a is the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and b is the volume percentage of asphalt mortar in the volume of mastic; (4) According to the relationship between the apparent relative density of the mineral powder, the specific gravity of the fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the volume percentage of asphalt mortar in the volume of mastic, the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is obtained; in the step (4), the relationship between the apparent relative density of the mineral powder, the specific gravity of the fiber, the density of asphalt, the ratio of the volume of mastic to the skeleton gap ratio of the coarse aggregate, and the volume percentage ratio of asphalt mortar in the volume of mastic to the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber in the SMA-13 asphalt mixture is as shown in Formula 2: In formula 2, A is the volume percentage of coarse aggregate, B is the volume percentage of fine aggregate, C is the volume percentage of mineral powder, D is the volume percentage of asphalt, and E is the volume percentage of fiber; ρ 矿 is the apparent relative density of mineral powder, ρ 纤 is the specific gravity of the fiber, ρ 沥 is the density of asphalt; (5) according to the apparent relative density of the mineral powder, the apparent relative density of the coarse aggregate and the apparent relative density of the fine aggregate, the sieve hole pass rate of the key-grade mineral material is obtained, and the sieve hole pass rate of the key-grade mineral material includes the sieve hole pass rate of the 4.75mm grade mineral material and the sieve hole pass rate of the 0.075 grade mineral material; according to the mass percentage of the first graded coarse aggregate and the sieve hole pass rate of the 4.75mm grade mineral material, the sieve hole pass rate of the 9.5mm grade mineral material is obtained; the sieve hole pass rate of the 16mm grade mineral material is obtained. The pass rate is 100%; according to the sieve hole pass rate of the key grade ore, the sieve hole pass rate of the 9.5mm grade ore and the sieve hole pass rate of the 16mm grade ore, the sieve hole pass rate of the remaining recommended grading grades of ore is obtained; the sieve hole pass rate of each grade ore of the recommended grading includes: the sieve hole pass rate of the 16mm grade ore, the sieve hole pass rate of the 9.5mm grade ore, the sieve hole pass rate of the 4.75mm grade ore, the sieve hole pass rate of the 0.075 grade ore and the sieve hole pass rate of each grade ore of the remaining recommended grading The sieve hole pass rate of the remaining recommended grading materials includes: 2.36mm sieve hole pass rate, 1.18mm sieve hole pass rate, 0.6mm sieve hole pass rate, 0.3mm sieve hole pass rate and 0.15 sieve hole pass rate; in the step (5), the calculation formula of the sieve hole pass rate of the 4.75mm sieve hole ore is shown in formula 3; the calculation formula of the sieve hole pass rate of the 0.075 sieve hole ore is As shown in formula 4; the calculation formula for the sieve pass rate of 9.5mm grade ore is shown in formula 5; the calculation formula for the sieve pass rate of 2.36mm grade ore is shown in formula 6; the calculation formula for the sieve pass rate of 1.18mm grade ore is shown in formula 7; the calculation formula for the sieve pass rate of 0.6mm grade ore is shown in formula 8; the calculation formula for the sieve pass rate of 0.3mm grade ore is shown in formula 9; the calculation formula for the sieve pass rate of 0.15mm sieve is shown in formula 10; 100-k(100-P 4.75 ) Formula 5; 0.7×(P 4.75 -P 0.075 )+P 0.075 Formula 6; 0.7 2 ×(P 4.75 -P 0.075 )+P 0.075 Formula 7; 0.7 3 ×(P 4.75 -P 0.075 )+P 0.075 Formula 8; 0.7 4 ×(P 4.75 -P 0.075 )+P 0.075 Formula 9; 0.7 5 ×(P 4.75 -P 0.075 )+P 0.075 Formula 10; In equations 3 and 4, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder; In formula 5, k is the mass percentage of the first graded coarse aggregate in the coarse aggregate, P 4.75 The passing rate of 4.75mm sieve hole for mineral materials; In formulas 6 to 10, P 0.075 The passing rate of 0.075mm sieve hole for mineral materials; In the step (5), after obtaining the sieve hole pass rate of each grade of the recommended gradation mineral material, the method further includes: obtaining a sieve hole pass rate range of each grade of the recommended gradation mineral material that meets the construction specification according to the sieve hole pass rate of each grade of the recommended gradation mineral material, and obtaining a sieve hole pass rate of each grade of the synthetic gradation mineral material that is closest to the sieve hole pass rate of each grade of the recommended gradation mineral material according to the sieve hole pass rate range of each grade of the recommended gradation mineral material that meets the construction specification; There is no time sequence restriction between steps (2) to (4) and step (5); (6) obtaining an initial asphalt-to-rock ratio according to the density of asphalt, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; obtaining a fiber content according to the specific gravity of fiber, the apparent relative density of mineral powder, the apparent relative density of coarse aggregate, and the apparent relative density of fine aggregate; and preparing a VVT by vertical vibration compaction method according to the initial asphalt-to-rock ratio, the sieve pass rate of each grade of mineral material of the recommended gradation, and the volume percentage ratio of asphalt, coarse aggregate, fine aggregate, mineral powder, and fiber in the SMA-13 asphalt mixture. M test piece; the VVTM test piece includes a first test piece, a second test piece and a third test piece, the oil-stone ratio of the first test piece is 0.2 to 0.4 less than the initial oil-stone ratio; the oil-stone ratio of the second test piece is the initial oil-stone ratio; the oil-stone ratio of the third test piece is 0.2 to 0.4 greater than the initial oil-stone ratio; in the step (6), when the VVTM test piece is made by the vertical vibration compaction method, it is carried out according to the initial oil-stone ratio and the sieve pass rate of each grade of synthetic grading mineral material; in the step (6), the calculation formula of the initial oil-stone ratio is as shown in formula 11: In formula 11, Dγ b is the density of asphalt, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder; In step (6), the calculation formula of the fiber content is shown in Formula 12: In formula 12, Eγ x is the specific gravity of the fiber, Aγ c is the apparent relative density of coarse aggregate, Bγ f is the apparent relative density of fine aggregate; Cγ k is the apparent relative density of mineral powder; (7) determining the gross volume density of the VVTM specimen, and obtaining the physical parameters of the VVTM specimen according to the gross volume density, wherein the physical parameters of the VVTM specimen include the coarse aggregate void ratio, the mineral void ratio and the specimen void ratio; when the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, selecting the VVTM specimen with the target void ratio of the SMA-13 asphalt mixture corresponding to the asphalt-stone ratio of the first specimen, the second specimen and the third specimen as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture; the design standard of the vertical vibration compaction method includes: the coarse aggregate void ratio of the VVTM specimen is less than the skeleton void ratio of the coarse aggregate, the mineral void ratio of the VVTM specimen is ≥14.5 and the specimen void ratio is 2.5-4; in step (7), determining the gross volume density of the VVTM specimen according to the "Highway Engineering Aggregate Test Procedure" T309-2005; When the first specimen, the second specimen and the third specimen do not simultaneously meet the design standard of the vertical vibration compaction method, the grading boundary values of the first graded coarse aggregate and the second graded coarse aggregate are reduced, and steps (2) to (7) are repeated until the first specimen, the second specimen and the third specimen simultaneously meet the design standard of the vertical vibration compaction method, and the asphalt-stone ratio of the specimen corresponding to the target void ratio of the SMA-13 asphalt mixture in the first specimen, the second specimen and the third specimen is selected as the optimal asphalt-stone ratio of the SMA-13 asphalt mixture.
2. The SMA-13 asphalt mixture VVTM volume design method according to claim 1 is characterized in that: In step (7), the physical parameters of the VVTM specimen also include one or more of asphalt saturation, Marshall stability and flow value; the vertical vibration compaction method design standard also includes: the asphalt saturation is 75-85%, the Marshall stability is ≥10kN and the flow value is 1.5-4mm. One or more.
3. The SMA-13 asphalt mixture VVTM volume design method according to claim 1, characterized in that: After step (7), the method further includes: designing an SMA-13 asphalt mixture according to the VVTM volume design method of steps (1) to (7), preparing an SMA-13 asphalt mixture sample by a vertical vibration compaction method, and testing the performance of the SMA-13 asphalt mixture sample; when the SMA-13 asphalt mixture sample does not meet the requirements of the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering", replacing one or more of asphalt, coarse aggregate, fine aggregate, mineral powder and fiber, re-designing the SMA-13 asphalt mixture according to the VVTM volume design method of steps (1) to (7), preparing an SMA-13 asphalt mixture sample by a vertical vibration compaction method, and testing the performance of the SMA-13 asphalt mixture sample; until the performance of the SMA-13 asphalt mixture sample meets the requirements of the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering"; The performance of the SMA-13 asphalt mixture sample includes at least one of high temperature stability, low temperature mechanical properties, water stability, leakage performance and scattering performance.
Citation Information
Patent Citations
Design method of AC-13 asphalt mixture
CN103147374A